Analisis Perkembangan Kurikulum Pendidikan Agama Islam: Dari KTSP 2006 Menjadi Kurikulum Merdeka - Az Zahra, Annida Luthfiyah; Kholwa, Adzra; Al Fikri, Haydar; Fadhil, Abdul (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2022)
The curriculum is an essential part of the world of education. In general, a curriculum is an educational tool that has the function to achieve learning objectives as well as a guide in carrying out the teaching and learning process. The purpose of this research is to find out the development of Islamic Religious Education and Moral Education subjects in the curriculum that has been implemented in Indonesia (KTSP, K-13, and merdeka belajar curriculum). The research method used is qualitative with a library research approach. Data collection techniques using literature studies and document studies. The results of the study show that several significant differences in the curriculum that have been implemented in Indonesia affect the learning process of Islamic Religious Education. This can be seen in terms of time allocation, goals, learning approaches, etc.